2017
DOI: 10.1186/s40645-017-0127-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and challenges of global high-resolution non-hydrostatic atmospheric simulations using the K computer

Abstract: This article reviews the major outcomes of a 5-year (2011-2016) project using the K computer to perform global numerical atmospheric simulations based on the non-hydrostatic icosahedral atmospheric model (NICAM). The K computer was made available to the public in September 2012 and was used as a primary resource for Japan's Strategic Programs for Innovative Research (SPIRE), an initiative to investigate five strategic research areas; the NICAM project fell under the research area of climate and weather simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 125 publications
0
34
0
Order By: Relevance
“…However, global convection‐permitting models (e.g., Satoh et al . ; Prein et al . ), and regional models (e.g., Marsham et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, global convection‐permitting models (e.g., Satoh et al . ; Prein et al . ), and regional models (e.g., Marsham et al .…”
Section: Introductionmentioning
confidence: 99%
“…For similar reasons, other global models (Fowler et al, 2017) also employ some degree of convective stabilization down to 3 km resolutions. However, global convection-permitting models (e.g., Satoh et al, 2017;Prein et al, 2017), and regional models (e.g., Marsham et al, 2013;Holloway et al, 2016) have shown clear improvements in the organization and propagation of mesoscale convective systems (MCSs) compared to models with parametrized convection, likely due to better coupling of the convective motions and microphysics with the large-scale flow (effect of cold pools, wind shear, memory and grid-scale motions being in phase with the condensational heating). These studies also suggested that the largest model sensitivity in the (5 km) resolution range is due to the use (or not) of a deep convection parametrization.…”
mentioning
confidence: 99%
“…Instead of requiring the user to produce a pair of low‐ and high‐resolution simulations simultaneously, it makes use of existing high‐resolution simulations. This sets a relatively low bar for carrying out such coarse‐graining studies, and makes use of the wealth of high‐resolution simulations available (Satoh et al ., ; ; Schalkwijk et al ., ; Heinze et al ., ). The coarse‐grained dataset is coupled to a forecast model through the use of a SCM framework.…”
Section: Discussionmentioning
confidence: 97%
“…Recent years have seen a surge in the production of very high‐resolution atmospheric simulations. The continued increase in computational power has led to an increase in domain size and duration of simulations, with resolutions regularly reaching convection‐permitting, if not convection‐resolving, scales (Holloway et al ., ; Satoh et al ., ; ; Schalkwijk et al ., ; Heinze et al ., ; Stevens et al ., ). The availability of such datasets opens up the option of using high‐resolution simulations as a proxy for the “true atmosphere” and identifying the difference between a low‐resolution forecast model and a high‐resolution simulation as the model error that a stochastic parametrisation seeks to represent (Shutts and Palmer, ; Shutts and Pallares, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Cascade project produced high-resolution convection-permitting simulations using the UK Met Office Unified Model (MetUM) at 1.5-km and 4-km resolution over a domain covering most of West Africa, and a domain spanning 15,500 km by 4,500 km over the Indian Ocean, Warm Pool and tropical west Pacific (Holloway et al, 2013;Marsham et al, 2011), while the High-Definition Clouds and Precipitation for advancing Climate Prediction [HD(CP) 2 ] project used the ICOsahedral Nonhydrostatic atmosphere model for a LES over Germany at 156-m resolution for 4 days (Heinze et al, 2017). The increase in production of extensive high-resolution data sets (Heinze et al, 2017;Holloway et al, 2012;Satoh et al, 2014Satoh et al, , 2017Schalkwijk et al, 2015) has largely become possible due to computational advances in recent years.…”
Section: Introductionmentioning
confidence: 99%